Examining the Effects of Perceptions of Police Effectiveness, Procedural Justice, and Legitimacy on Racial Differences in Anticipated Cooperation With Law Enforcement in Pennsylvania - Kruis, Nathan E. (Criminal justice policy review, 2023)
Perceptions of law enforcement ineffectiveness, injustice, and illegitimacy are prevalent among individuals living in Black communities in the United States. Prior research links these attitudes with differential orientations toward cooperation with police. The current study used data collected from a representative sample of 522 Pennsylvania residents to measure public perceptions of police. Analyses examined racial differences in perceptions of police and determined whether normative (i.e., perceptions of procedural justice) and/or instrumental (i.e., perceptions of police effectiveness) assessments of police could explain racial differences in anticipated cooperation with law enforcement through perceptions of legitimacy. Findings revealed the presence of a significant indirect relationship between race and perceptions of legitimacy through perceptions of police effectiveness and procedural justice, as well as a significant indirect relationship between race and cooperation through police effectiveness, procedural justice, and legitimacy. Theoretical and practical implications stemming from these findings are discussed within.